2019
DOI: 10.3835/plantgenome2019.06.0042
|View full text |Cite
|
Sign up to set email alerts
|

Profiling SNP and Nucleotide Diversity to Characterize Mekong Delta Rice Landraces in Southeast Asian Populations

Abstract: The Plant Genome R ecent advances in genomic analysis methods can be exploited to shed light on the genetic diversity of various crops, not only that of representative major resources, known as core collections (Gepts, 2006; Phan et al., 2019; Wang et al., 2014), but also minor resources in local collections not yet thoroughly characterized. Such evaluation of crop plant genomic structures may reveal useful resources and/or unique characteristics hidden in local collections (Hermisson and Wagner, 2004;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Numerous techniques can be used to determine rice genetic variations in order to comprehend and use accessible gene bank accessions. Initially, isozyme markers were used to evaluate rice genetic diversity [12]; however, these have now been replaced with DNA markers, such as simple sequence repeats (SSRs), microsatellites [13,14], and single nucleotide polymorphisms (SNPs) [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous techniques can be used to determine rice genetic variations in order to comprehend and use accessible gene bank accessions. Initially, isozyme markers were used to evaluate rice genetic diversity [12]; however, these have now been replaced with DNA markers, such as simple sequence repeats (SSRs), microsatellites [13,14], and single nucleotide polymorphisms (SNPs) [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings suggested that lower genetic diversity was experienced in a recent bottleneck during the domestication selection of the waxy locus in the waxy rice genome [69][70][71]. On the other hand, the remaining cultivated subgroups, indica, aus, and admixture (representing higher diversity landrace, weedy, and bred groups in another way) were higher in nucleotide diversity than that of the wild group, suggesting positive artificial selection due to the high π-value regions in each of these classified populations [68].…”
Section: Discussionmentioning
confidence: 97%
“…Of which, many starch synthesis genes have been studied on their genetics and genomics [47,66] but GBSSII is the only exception. Analysis of nucleotide diversity is important to highlight the functional importance of genomic regions [67] and it has also appeared to be useful to characterize local populations, representing the whole genome distribution of each population using π-values [68]. In our study, the nucleotide diversity analysis based on the classified ecotypes of 475 rice accessions revealed the lowest diversity values in japonica ecotypes (temperate japonica, 0.0029, and tropical japonica, 0.0030) despite the wild group representing its lowest diversity value (0.0045) on a variety basis, suggesting no significant differences between the wild group and any of the identified cultivated subgroups (Figure 3 and Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-seven rice accessions consisting of 79 landraces and 18 improved accessions were selected from the Genebank of Mekong Delta Development Research Institute (MDI), Can Tho University, Vietnam (Supplementary Table 1) (Tam et al 2019). 'Nipponbare' and 'Pokkali' were added as sensitive and tolerant cultivar controls, respectively, for salinity stress.…”
Section: Plant Materialsmentioning
confidence: 99%
“…In this study, we investigated the salt tolerance and physiological characteristics of a diverse panel of landrace rice accessions cultivated in the Mekong Delta region (Tam et al 2019). We focused on the rice landrace variety 'Doc Phung', known to be particularly resistant to salt in the Mekong Delta (Ho et al 2018;Le 1999;Tin et al 2021).…”
mentioning
confidence: 99%